2008
DOI: 10.1007/s11237-008-9002-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and anomalous temperature dependence of the kinetic isotope effect of reactions of cycloalkanes C5H10, C6H12 and C6D12 with OH radicals in aqueous solutions

Abstract: in aqueous solution and in the gas phase has opposite signs. Values for the KIE and k 6 /k 5 decrease with increasing temperature from 5 to 55°C in the gas phase, while these values increase in solution. We propose that this phenomenon is a consequence of a solvent cage effect.The reactions of hydroxyl radicals with hydrocarbons play an important role in biochemical processes and the chemistry of the atmosphere and natural water supplies [1][2][3][4]. The kinetics of the reactions of OH radicals with saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The values for (KIE) l and (k A /k B ) l are the same for the reactions of cycloalkanes with HOONO and OH radicals in aqueous solution [13] in the temperature range studied (Table 1). An anomalous increase in KIE with increasing temperature is observed for both reactions.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The values for (KIE) l and (k A /k B ) l are the same for the reactions of cycloalkanes with HOONO and OH radicals in aqueous solution [13] in the temperature range studied (Table 1). An anomalous increase in KIE with increasing temperature is observed for both reactions.…”
Section: Resultsmentioning
confidence: 89%
“…The temperature dependence of the KIE for the c-C 6 H 12 /c-C 6 D 12 pair is described by the following equation According to our previous work [12], the value of KIE for all the reactions studied in solution with oxidizing agents, electrophiles, and metal complexes (except liquid-phase reactions with OH radicals [13]), is greater than unity and decreases with increasing temperature E D -E H > 0. The values of (KIE) g and (k 6 /k 5 ) g in the gas-phase reactions of hydrocarbons with PA studied in the present investigation decrease with increasing temperature (Table 1) in accord with Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Important additional information on mechanism can be obtained by studying the temperature dependence of the rate constant and substrate selectivity (rate constant ratios) for a broad range of hydrocarbons [13]. In recent work [14], we have shown that the temperature dependence of the KIE in gas-phase and liquid-phase reactions of cyclohexane (c-C 6 H 12 /C 6 D 12 ) with the OH radical at 5-55°C have opposite signs: the KIE values in the gas phase drop with increasing temperature, while these values increase in water. These discrepancies are presumably a consequence of the solvent cage effect.…”
mentioning
confidence: 99%